2016
DOI: 10.1016/j.neo.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of PCAT14 as Prognostic Biomarker in Prostate Cancer

Abstract: Rapid advances in the discovery of long noncoding RNAs (lncRNAs) have identified lineage- and cancer-specific biomarkers that may be relevant in the clinical management of prostate cancer (PCa). Here we assembled and analyzed a large RNA-seq dataset, from 585 patient samples, including benign prostate tissue and both localized and metastatic PCa to discover and validate differentially expressed genes associated with disease aggressiveness. We performed Sample Set Enrichment Analysis (SSEA) and identified genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…SChLAP1 increases with progression of PCa and predicts poor prognosis of patients with PCa [11, 12]. More importantly, these cancer-related lncRNAs can be detected in body fluids, such as blood and urine [13, 14], which makes them ideal diagnostic and prognostic biomarkers for cancer patients. However, previous studies focused mainly on the diagnostic value of SChLAP1 in tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…SChLAP1 increases with progression of PCa and predicts poor prognosis of patients with PCa [11, 12]. More importantly, these cancer-related lncRNAs can be detected in body fluids, such as blood and urine [13, 14], which makes them ideal diagnostic and prognostic biomarkers for cancer patients. However, previous studies focused mainly on the diagnostic value of SChLAP1 in tissue [15].…”
Section: Introductionmentioning
confidence: 99%
“…PCAT-14 is commonly up-regulated in primary tumors. PCAT14 is an AR-regulated transcript while PCAT14 is highly expressed in low grade disease and loss of PCAT14 predicts for disease aggressiveness and recurrence, and its overexpression suppresses invasion of PCa cells [45]. PCAT14 lower expression is signi cantly prognostic for multiple clinical endpoints supporting its signi cance for predicting metastatic disease that could be used to improve patient management [46].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Maher’s group [79,80] has reported that an aberrant downregulation of prostate cancer associated transcript-14 (PCAT-14) was associated with Gleason score and a greater probability of metastatic progression, overall survival, and prostate cancer-specific mortality across multiple independent datasets and ethnicities. Moreover, studies in in vitro cell cultures demonstrated that a downregulation of PCAT14 increased cell migration while an overexpression reduced cell growth, migration and invasion, suggesting that PCAT14 may possess a significant biological role in PCa tumorigenesis and progression, and may function as a potential biomarker for PCa detection and prognosis.…”
Section: Potential Lncrna Biomarkers Under Investigationmentioning
confidence: 99%